The potential of biodegradable polymers: Chitosan, polyethylene glycol, and polycaprolactone as materials for progesterone intravaginal devices - Elma Yuliani Yessa; Ietje Wientarsih; Mokhamad Fakhrul Ulum; Bambang Purwantara; Amrozi Amrozi (Livestock and Animal Research, 2024)
For several decades, a protocol based on the use of progestagens has been used to manage livestock reproduction with minimal alterations. Recently, researchers have gained insight into the short-term use of progestagen protocols lasting 5-7 days, which has been found to reduce the incidence of vaginitis and obviate the use of antibiotics. Additionally, this approach enables the reutilization of silicone-based devices such as CIDRs after a thorough biosecurity assessment. However, these devices have certain limitations. At the end of the treatment, they must be disposed of and cannot be reused, necessitating a re-evaluation of their use for technical and societal reasons, including animal health and welfare, food safety, and environmental impact.A chitosan-PEG intravaginal implant formulation released progesterone for a period of four days, corresponding to the degradation time of the implant in the vagina. The use of a simple melting and molding process for the combination of PCL-PEG-chitosan implants has been observed to result in degradation of both simulated vaginal fluid and vaginal tissue of cows. The development of intravaginal devices made from biodegradable polymers is considered a potential solution because these materials would degrade within the body, eliminating the need for removal and leaving no residue. These devices are safe for animals and the environment.